Nature's defense against emerging neurodegenerative threats: Dynamic simulation, PCA, DCCM identified potential plant-based antiviral lead targeting borna disease virus nucleoprotein. - Noimul Hasan Siddiquee; Md Ifteker Hossain; Farhana Mansoor Priya; Sakia Binte Azam; Md Enamul Kabir Talukder; Durjoy Barua; Salina Malek; Niloy Saha; Sidratul Muntaha; Ridoy Paul; Israt Jahan Ritu; Farjana Islam Tuly; et al. (PLoS ONE)
The rare zoonotic Borna disease virus (BDV) causes fatal neurological disease in various animals, with a high mortality rate exceeding 90% in central Europe. However, unlike most viruses, it establishes persistent infections within the host cell nucleus, hindering treatment. As successful BDV treatments remain elusive, the researchers turned to a computational approach, utilizing molecular docking, ADME/T, post-docking MMGBSA, MD simulation, DCCM, and PCA to identify promising phytochemical drug candidates targeting the BDV Nucleoprotein (PDB ID: 1N93). From IMPPAT 1940 unique phytochemical compounds of a total of 8617 compounds from 36 Indian medicinal plants were retrieved. Three compounds were chosen as leads with higher binding affinity of -6.244, -6.116, and -6.07 kcal/mol with CID 163114683 (IMPHY000668) Nimbochalcin, CID 20871246 (IMPHY007896) 3,4-Dihydroxy-5-oxocyclohex-3-ene-1-carboxylic acid, and CID 243 (IMPHY002962) Benzoic acid. The three top compounds coordinated with the protein's common amino acid residues at GLN 161, ARG 165, ILE 145, ILE 162, ILE 149, and VAL 229 during molecular docking, which implies that both lead compounds and the control ligand interact within the protein's shared active site. Afterwards, negative binding free energies of Nimbochalcin, 3,4-Dihydroxy-5-oxocyclohex-3-ene-1-carboxylic acid, and Benzoic acid were -51.21, -13.94, and -22.95 kcal/mol, accordingly. Favorable Pk and toxicological characteristics are shared by all of the chosen drugs, indicating their efficacy and safety. Using MD simulation, these three compounds were further assessed, and their stability in binding to the target protein was confirmed and subsequently, DCCM and PCA analyses were carried out from MD trajectory. MD simulations found that the protein binding site is highly stable when complexed with CID 20871246 and has a higher negative binding free energy value, indicating a strong interaction between the compound and the protein. Principal component analysis (PCA) identified three main components (PC1, PC2, and PC3) that accounted for 53.43%, 12.31%, and 5.97% of the variance, respectively. These findings provide intriguing evidence that the CID 20871246-1N93 complex is more stable than the other complexes. The BDV nucleoprotein was the target of this study's investigation where CID 20871246 (3,4-dihydroxy-5-oxocyclohex-3-ene-1-carboxylic acid) exhibited tremendous antiviral activity which is found in the flower of the plant Mangifera indica revealing as a possible therapeutic candidate.